Water masses and circulation in the surface layers of the Caribbean at 66ºW - Hernández-Guerra, Alonso; Joyce, Terrence (Geophysical Research Letters, 2015)
A meridional hydrographic section was made in August–September 1997 at 66°W from the coast of Venezuela to Woods Hole aboard the R/V Knorr. In this report, we concentrate on near surface measurements in the Caribbean. The data show two distinct water masses with different origins. From approximately 14°N to Puerto Rico, Caribbean Surface Water and Subtropical Under Water with their source in the North Atlantic are found, as previously observed. From Venezuela to approximately 13°N, a less saline water mass with its source in the Tropics and South Atlantic is found. Within the southern portion of the section, two different velocity patterns are observed, namely, an eastward flow with a subsurface maximum near the coast of Venezuela, and a surface intensified westward jet with Velocities of 130 cm s−1 in midbasin.